Catalytic hydrogenation of stearic acid to 1-octadecanol using supported bimetallic Pd–Sn(3.0)/γ–Al2O3 catalyst - Elisa Hayati; Atina Sabila Azzahra; Rodiansono Rodiansono (Jurnal Kimia Sains dan Aplikasi, 2022)
Supported bimetallic palladium-tin catalyst on gamma-alumina (γ-Al2O3) (denoted as Pd–Sn(3.0)/γ-Al2O3; Pd = 5%wt and Pd/Sn molar ratio is 3.0) has been synthesized via the hydrothermal method at a temperature of 423 K for 24 h and reduced with H2 at 673 K for 3 h. The XRD patterns of the samples showed typical diffraction peaks of support γ-Al2O3, metallic Pd, Sn, and Pd–Sn alloy phases. Diffraction peaks of metallic Pd were observed at 2θ = 39.8°; 46.6°; and 68.0°, which can be attributed to the Pd(111), Pd(200), and Pd(220), respectively, while the diffraction peaks at 2θ = 39.8° and 41.0° can be attributed to Pd2Sn and Pd3Sn2, respectively, which may overlap with the Pd(111) species. The ammonia desorption and pyridine adsorption profiles showed Lewis and Brönsted acid sites. The specific surface area (SBET) of Pd–Sn(3.0)/γ-Al2O3 catalyst was 117.83 m2/g which is dominated by a micropore structure. The highest conversion of stearic acid was 99.1% with a yield of 1-octadecanol 43.2% was obtained at temperature 513 K, initial H2 pressure of 2.0 MPa, a reaction time of 13 h, and in 2-propanol/water (4.0:1.0 v/v) solvent.